Role of short course intravenous methylprednisolone in the management of sudden sensorineural hearing loss - Gupta, Saurabh; Gyawali, Bigyan Raj; Pradhananga, Rabindra Bhakta; Rayamajhi, Pabina (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Steroids have proven efficacy in the management of sudden sensorineural hearing loss (SSNHL); however, the mode of delivery and the duration of the treatment varies amongst different centres and a consensus is yet to be established. The aim of this study was to determine the efficacy of short course intravenous methylprednisolone in the management of SSNHL. Methods: This retrospective study was conducted in the department of ENT and head and neck surgery, TUTH, institute of medicine, Kathmandu, Nepal. Record data of the cases from January 2019 to May 2020, who met the criteria of SSNHL and had received intravenous methylprednisolone for three days, were assessed for the demographic profile, duration and degree of hearing loss, co-morbidities, and hearing improvement after the therapy. Cases with incomplete documentation were excluded. Pre-admission and three days post steroid therapy pure tone audiogram investigation were compared to see the improvement retrospectively. Institutional review committee clearance was taken. Results: Out of 32 patients, the male: female ratio was 1.7:1. Mean hearing loss prior to intravenous Methylprednisolone was 77.84 dB whereas mean hearing loss three days post intravenous methylprednisolone was 69.41dB. Three patients had complete recovery, sixteen had partial recovery and thirteen had no recovery after giving three days of intravenous methylprednisolone. Conclusions: Short course intravenous methylprednisolone is effective in the treatment of SSNHL with minimal side effects.